KEMAMPUAN MULTIREPRESENTASI DAN HUBUNGANNYA DENGAN HASIL BELAJAR MAHASISWA CALON GURU FISIKAJAR MAHASISWA - Nurhayati Nurhayati; Nurussaniah Nurussaniah; Anita Anita (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
Representation is an inseparable part of science, and research shows that the representation ability of preservice physics teachers was still inadequate. This study evaluated preservice physics teachers’ multiple representation ability and the relationship between the ability with the overall student learning outcomes or the Cumulative Achievement Index (GPA). There was a diference in multiple representation ability based on the level of education programs (fourth semester and sixth-semester students), and the ability significantly correlated with preservice physics teachers learning outcomes.